Efikasi Diri dan Kesiapsiagaan Perawat Rumah Sakit terhadap Bencana: Self-Efficacy and Preparedness of Hospital Nurses for Disasters - Ferdy Lainsamputty; I Gede Purnawinadi; Raden Bagus Edy Santoso; Vidya Angeline Babu (Fakultas Keperawatan Universitas Andalas, 2022)
Disasters can be caused by natural, non-natural, and human factors, resulting in human casualties, environmental damage, property losses, and psychological impacts. Good self-efficacy for nurses has the potential to increase disaster preparedness. This study aimed to examine the relationship between self-efficacy and disaster preparedness among hospital nurses. This was a descriptive correlational study with cross sectional approach. A convenience sampling technique was applied to recruit 152 nurses from a general hospital in Central Sulawesi Province of Indonesia. The questionnaires were General Self Efficacy (GSE) and Disaster Preparedness Evaluation Tool (DPET). Spearman Rank Correlation was used to test the relationship between these variables. There was no significant relationship between self-efficacy and disaster preparedness (r=0.213; p=0.102). In general, self-efficacy did not significantly contribute to the disaster preparedness of hospital nurses. The lack of disaster experience has the potential to mediate nurses' confidence in disaster preparedness. Consistency of nurses' beliefs in facing challenges and difficulties related to disasters needs to be maintained, but it is also necessary to improve the ability to get more ideas in solving them. Effective interventions to improve disaster preparedness such as basic training and routine simulations are highly recommended.